Gender Role Construction and Indian Newspapers: Study on the Colonial Period - Mukherjee, Moloy (Unisia, 2025)
During the colonial period in India, newspapers were instrumental in shaping gender roles, reflecting the complex interplay between colonial policies and indigenous cultural norms. Newspapers like Amrita Bazar Patrika, The Bengal Gazette, and The Hindu were key players in this discourse. These publications often reinforced patriarchal ideals, portraying women primarily as custodians of tradition and morality. For instance, Amrita Bazar Patrika in the late 19th century frequently featured editorials that advocated for women's education but within the confines of their roles as wives and mothers. The Bengal Gazette reported on the controversies surrounding the Age of Consent Act of 1891, where debates on women's rights were framed in a manner that upheld male authority. Similarly, The Hindu provided coverage on the Swadeshi movement, highlighting the role of women as symbols of the nation, thereby linking their identity to nationalist ideals. These newspapers not only reflected but also shaped public opinion, often limiting the discourse on gender roles to fit the broader nationalist and colonial agendas. This study delves into how these publications constructed and propagated gender norms, examining specific incidents like the coverage of the Rukhmabai case in The Times of India, which sparked nationwide debates on women's autonomy and the legal rights of women within marriage. By analyzing these historical texts, the research uncovers the ways in which the colonial-era press contributed to the enduring gender stereotypes in Indian society.